ANALISIS NON PERFORMING LOAN DAN KUALITAS ASET PRODUKTIF TERHADAP PROFITABILITAS PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI OJK - Kristina, Kristina; Efriyenti, Dian (SCIENTIA JOURNAL, 2021)
The average number of non-performing loans in this study is greater than 7% and the quality of earning assets is greater than 8%, so this research was conducted with the aim of investigating the impact of NPL and KAP on Return On Assets in banking companies registered with the Financial Services Authority. The data used is in the form of secondary data, namely published quarterly financial reports. population taken from banking companies (Bank Perkreditan Rakyat) in the 2015-2019 period as many as 27 data. Samples that meet the criteria are 3 data. Based on the results of the analysis partially or the t test: (1) NPL partially has a negative but insignificant effect on ROA, it is known that tcount -1.342 <ttable -2.00247 and a significance of 0.185> 0.05, (2) KAP partially had a negative but not significant effect on ROA with tcount -0.323 <ttable -2.00247 and a significance of 0.748> 0.05. Simultaneously or f test: NPL and KAP have a significant effect on ROA with a value of Fcount 10.222> Ftable 3.16 and a significance of 0.000 <0.005.